Methodological Choice and Design Scholarship, Policy and Practice in Social and Educational Research - Markauskaite, Lina.; Freebody, Peter; Irwin, Jude.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Beginning and well-seasoned researchers alike face major challenges in understanding the complexities of research designs arising from within and across methodological paradigms as well as in applying them in ways that maximize impact on knowledge, practice and policy. This volume offers crucial reinterpretations of established research methodologies in light of contemporary conditions. It also presents a critical introduction to some contemporary research approaches yet to gain general recognition. It charts and analyzes the conceptual and practical complexities of a variety of research designs for contemporary educational and social work research, providing readers what they need not only to design technically sound and coherent research studies but also to develop methodologically innovative research projects that cross the boundaries between different methodological traditions to the benefit of scholarship, policy, and practice.
Part I: Introduction to the book and overview: I.1: Bridging and blending disciplines of inquiry: Doing science and changing practice and policy: Lina Markauskaite, Peter Freebody Jude Irwin -- Part II: Foundations: II.1: Research methods for scholarship, practice and policy: Peter Freebody, Lina Markauskaite, Jude Irwin -- Part III: Research approaches for innovation and action-focussed inquiry: III.1: Design-based research: We need to do better: Peter Reimann -- III.2: Design experiments: Their relevance and importance for educational research: Richard Walker -- III.3: Action research in education and social work: Susan Groundwater-Smith and Jude Irwin -- III.4: Linking practitioner action, innovation and decision-making: Practical challenges and contraints: Robyn Ewing -- III.5: Ethnomethodology and classroom interaction: Applications and challenges: Peter Freebody -- III.6: Ethnomethodology: From the analysis of classroom interaction to policy and school reform: Michael Anderson -- III.7: Negotiated ethnography: The possibilities for practice: Debra Hayes -- III.8: Working through the difficulties in negotiated ethnography: Ken Johnston -- III.9: Drawing on the arts, transforming research: Possibilities of arts-informed perspectives: Andra Cole and Gary Knowles -- III.10: Arts-informed inquiry: Investigating the liminal in professional education: Robyn Ewing -- Part IV: Classical research methods in new social and political contexts: IV.1: Historical analysis: New approaches to postcolonial scholarship: Tim Allender -- IV.2: Postcolonial scholarship in social justice research: Ruth Phillips -- IV.3: Postpositivist policy anlysis: Analysing policy as discourse: Susan Goodwin -- IV.4: The importance of policy failure: Phillip Jones -- IV.5: Thinking comparatively: Anthony Welch -- IV.6: Know Thyself: Culture and identity in comparative research: Nigel Bagnall -- IV.7: Quantative modelling of correlational data in educational research: Andrew J. Martin -- IV.8: From quantative modelling to experimentation in educational research: Paul Ginns -- Part V: Methodological frontiers: challenges and future directions: V.1: Digital knowledge and digital research: What could eResearch offer for education and social policy? Lina Markauskaite -- V.2: Afterword: Emerging methodological challenges for educational research: Peter Goodyear -- V.3: Afterword: Challenges and futures for social work and social policy research methods: Barbara Fawcett, Sue Goodwin, Ruth Phillips -- V.4: Epilogue: Towards an integrated research agenda: Education for social change and social change for education: Jude Irwin, Peter Freebody, Lina Markauskaite.
Keywords: Social sciences; Social sciences -- Methodology; Social work; Psychological tests and testing; Social Sciences; Methodology of the Social Sciences; Education (general).; Social Work; Social Sciences, general; Psychological Methods/Evaluation.